Enhanced survival fractions of UV-irradiated spores in clusters on a surface in air: Measured and mathematically modeled results at 254-nm. Issue 6 (3rd June 2023) - Hill, Steven C.; Doughty, David C.; Mackowski, Daniel W.; Rastogi, Vipin; Eversole, Jay D.; McGrady, Dan; Handler, Frank; Kesavan, Jana
Abstract: Germicidal ultraviolet light (GUV) is routinely used to kill pathogenic bacteria and viruses for limiting the transmission of disease. Microbes such as bacterial spores can form aggregates either with themselves or other particles. These aggregates can shield organisms within them from GUV and thus make it difficult to achieve a desired reduction in viability. There is a need to better understand shielding of microbes from UV, and how it depends upon particle size and composition. To determine the survival fractions of spores in clusters ( S p ) we aerosolized Bacillus anthracis Sterne spores, collected the clusters onto a surface, illuminated the samples with the desired fluence (J/m 2 ) of 254-nm GUV, then resuspended the spores, plated serial dilutions and counted live colonies. The S p was calculated for each time point using the culturable organisms in the exposed and unexposed samples. We also modeled the S p of spores in clusters on a surface in air. In these mathematical models, each spore was approximated as a homogenous sphere having optical properties approximating those of spores. The absorption of GUV by each sphere within the cluster resting on a surface was calculated using the Multi-Sphere T-Matrix (MSTM). Plots showing both measured and calculated S p versus GUV fluence illustrate similarities between measured and calculated values and increases in S p with cluster size. These studies add to the evidence that particle sizes need to be considered when modeling, designing, and using GUV systems to reduce spreading of infectious disease. The potential relevance to 222-nm GUV inactivation is discussed. Graphical Abstract: UF0001